2020
DOI: 10.1101/2020.01.07.896910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ecological assembly processes of the bacterial and fungal microbiota of wild and domesticated wheat species

Abstract: Plant domestication has led to substantial changes in the host physiology. How this anthropogenic intervention has contributed in altering the wheat microbiota is not well understood. Here, we investigated the role of ecological selection, drift and dispersal in shaping the bacterial and fungal communities associated with domesticated wheat Triticum aestivum and two wild relatives, Triticum boeoticum and Triticum urartu. O… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…We observed a stronger selection of bacterial and fungal communities at the later growth stages based on the more distinct clustering of samples at BBCH21. Landraces and ancient lines of wheat clustered more distinctly at later stages, which could indicate a stronger selection during the colonization of ancient lines, as was also observed in a recent study (Hassani et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We observed a stronger selection of bacterial and fungal communities at the later growth stages based on the more distinct clustering of samples at BBCH21. Landraces and ancient lines of wheat clustered more distinctly at later stages, which could indicate a stronger selection during the colonization of ancient lines, as was also observed in a recent study (Hassani et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…Rossmann et al (2020) observed stronger interactions in landraces with their soil microbiomes compared to modern wheat. Hassani et al (2020) found a higher stochasticity in the assembly of microbial communities in modern wheat compared to the two ancestors T. boeoticum and T. urartu. With a lower immigration rate, we also expected lower alpha diversity, and indeed, we observed that Tm and Tt had the lowest alpha diversity.…”
Section: Discussionmentioning
confidence: 86%
“…Cereal related grasses show high stochasticity in the assembly of endophytic microbiota [ 2 , 15 ]. Given the high stochasticity of microbial community assembly and the heterogeneous growth habitats of these plants, they are prone to accumulate highly heterogeneous microbiomes.…”
Section: Discussionmentioning
confidence: 99%
“…Wild plants are far more diverse and are grown under a much wider range of conditions than crop plants, entailing that FECs in wild species might be enriched for beneficial taxa. For example, FECs from bread wheat ( Triticum aestivum ) were less diverse than FECs from the closely related Triticum urartu [ 15 ]. To fully evaluate the true potential of wild species FECs for crop improvement, it is necessary to analyze FECs in population of wild species and compare them with those of related crops.…”
Section: Introductionmentioning
confidence: 99%
“…According to their model, beta-null deviation values close to zero indicate neutral assembly, and values that are different from zero as niche-based assembly. Furthermore, Tucker et al's framework has been applied in a study that investigated the response of soil microbial communities to an anthropogenic disturbance (10) and in another that explored the role of ecological selection, drift and dispersal in assembling the bacterial communities associated with domesticated and wild wheat species (17).…”
Section: Introductionmentioning
confidence: 99%